Helminthiasis saluran cerna pada sapi perah - ZALIZAR, LILI (Faculty of Animal Science, Universitas Brawijaya, 2017)
The purpose of this research was to find out prevalence and the rates of helminthsinfection and the kind of the helmints on dairy cows that was belonging KUBE MajuMapan Cooperative in Jabung, Malang. A total of 123 dairy cows on farms wasinvestigated for the possibility of a worm infection. Indications of worm infectionswas based on faecal worm egg discovery using floating method using saturated saltsolution for nematode and cestode worms and sedimentation methods for theexamination of worms trematodes. Examination of the number of worm’s eggs useWhit lock chambers tool. Stool examination was done in the Laboratory of AnimalHealth belong to the Department of Animal Husbandry East Java Province in thedistrict of Pakis Malang. The sample examination was done in 3 (three) timesrepetition.The results showed there are 2 (two) types of worm eggs, nematodetype Strongyloid sp and Trematodes type Fasciola sp. The prevalence ofStrongyloid infection in cattle is large enough that is equal to 33.33 percent (41of 123 dairy cows). While the prevalence of the infected cattle Fasciola sp only23.58 percent (29 of 123 dairy cows). The rate of infection or mean number ofeggs per gram of feces of Strongyloid and Fasciola sp are only 2.43 and 1.88 per head of cattle. The efforts for worm medication regularly conducted by theCooperative has been able to reduce the prevalence of the disease and the ratesof infection